2022
DOI: 10.3346/jkms.2022.37.e351
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in Korea: Past, Present, and the Way Forward

Abstract: Since its first emergence in late 2019, severe acute respiratory syndrome coronavirus-2 has claimed more than 6.5 million lives worldwide and continues to infect hundreds of thousands of people daily. To combat this once-in-a-century disaster, several vaccines have been developed at unprecedented speeds. Novel vaccine platforms (messenger ribonucleic acid vaccines and adenoviral vector vaccines) have played a major role in the current pandemic. In Korea, six vaccines, including a domestically developed recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 85 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…However, recommendations for booster vaccination in populations that became infected after booster vaccination are still foggy. 14 …”
Section: Discussionmentioning
confidence: 99%
“…However, recommendations for booster vaccination in populations that became infected after booster vaccination are still foggy. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that vaccination triggers the body's immune response, which generates specific antibodies and cellular immunity that can reduce the risk of COVID-19 infection, particularly severe cases and fatalities 27,28 . Vaccination also helps decrease the duration of infection and reduces the risk of viral transmission 29,30 . These antibodies can neutralize the virus, prevent further infection of human cells, and assist other immune cells in eliminating the infected virus.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals may still contract the virus after vaccination, which could be due to the imperfect efficacy of the vaccine or variations in the immune responses of individuals. Studies have also suggested that new virus variants may challenge the protective efficacy of existing vaccines, and previous vaccines may have significantly reduced efficacy against the Omicron variant 30,31 . Thus, even after vaccination, individuals should continue to follow public health guidelines, such as wearing masks, maintaining social distancing, and practicing good hand hygiene, to further reduce the risk of infection and protect themselves and others from the consequences of virus transmission 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a difference in that the South Korean vaccination guidelines did not include any directions for healthcare workers (HCWs). 2 3 …”
Section: Introductionmentioning
confidence: 99%